TANTANGAN PERGURUAN TINGGI DALAM ERA PERSAINGAN GLOBAL - M. Kadarisman (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2011)
AbstractThe university’s challenge in the era of globalization is characterized by the development ofscience and technology which is full of competition. Sooner or later, universities inIndonesia in the future will face challenge to improve quality of educational institutionsthat must produce qualified human resources and advantages in various aspects of life.College is one of the subsystems of national education that cannot be separated from othersubsystems within and outside the education system. Universities are able to develop atleast five forms of intelligence, namely intellectual, emotional intelligence, practicalintelligence, social intelligence and spiritual intelligence as well as moral. The five forms ofthis intelligence must be developed simultaneously. If well done, then not only producestudents and graduates who are intellectually smart, but also smart in other things.Keywords: Globalization of Education, Science, Quality of Human Resources.